Bmal1‐deficiency affects glial synaptic coverage of the hippocampal mossy fiber synapse and the actin cytoskeleton in astrocytes. Issue 5 (19th November 2019) - Ali, Amira A. H.; Schwarz‐Herzke, Beryl; Rollenhagen, Astrid; Anstötz, Max; Holub, Martin; Lübke, Joachim; Rose, Christine R.; Schnittler, Hans‐Joachim; von Gall, Charlotte
Abstract: Bmal1 is an essential component of the molecular clockwork, which drives circadian rhythms in cell function. In Bmal1‐deficient (Bmal1−/−) mice, chronodisruption is associated with cognitive deficits and progressive brain pathology including astrocytosis indicated by increased expression of glial fibrillary acidic protein (GFAP). However, relatively little is known about the impact of Bmal1‐deficiency on astrocyte morphology prior to astrocytosis. Therefore, in this study we analysed astrocyte morphology in young (6–8 weeks old) adult Bmal1−/− mice. At this age, overall GFAP immunoreactivity was not increased in Bmal1‐deficient mice. At the ultrastructural level, we found a decrease in the volume fraction of the fine astrocytic processes that cover the hippocampal mossy fiber synapse, suggesting an impairment of perisynaptic processes and their contribution to neurotransmission. For further analyses of actin cytoskeleton, which is essential for distal process formation, we used cultured Bmal1−/− astrocytes. Bmal1−/− astrocytes showed an impaired formation of actin stress fibers. Moreover, Bmal1−/− astrocytes showed reduced levels of the actin‐binding protein cortactin (CTTN). Cttn promoter region contains an E‐Box like element and chromatin immunoprecipitation revealed that Cttn is a potential Bmal1 target gene. In addition, the level of GTP‐bound (active) Rho‐GTPase (Rho‐GTP) was reduced in Bmal1−/− astrocytes. In summary, our data demonstrate that Bmal1‐deficiency affects morphology of the fine astrocyte processes prior to strong upregulation of GFAP, presumably because of impaired Cttn expression and reduced Rho‐GTP activation. These morphological changes might result in altered synaptic function and, thereby, relate to cognitive deficits in chronodisruption. Main points: Astrocytic coverage of MFB is reduced in Bmal1−/− mice, which might contribute to cognitive deficits observed upon chronodisruption. Bmal1−/− astrocytes show impaired stress fiber formation, reduced cortactin expression and Rho‐GTP activity.